Efeito da Ativina-A e do Hormônio Folículo Estimulante (FSH) sobre o desenvolvimento in vitro de folículos pré-antrais bovinos - Silva, Anderson Weiny Barbalho (2012)
The aim of this study was to evaluate the effect of FSH alone or in combination with activin-A on survival, growth and expression of mRNA for ActR- IB, ActR- IIB, FSH-R, PCNA, and HAS1/2/3 in bovine secondary follicles cultured in vitro for 18 days. Preantral follicles (~0,2mm) were isolated from the cortex of bovine ovaries and individually cultured in the absence (control medium) or presence of activin-A alone at concentrations of (100ng/mL); FSH alone in increased concentrations - 50ng/mL (from day 0 to day 6), 100ng/mL (from day 7 to day 12), and 200ng/mL (from day 13 to day 18) or in association with activin-A in the same concentrations. After 18 days in vitro, follicles cultured with FSH showed a significant increase in diameter compared to the other treatments. On the other hand, the activin-A alone did not increase follicular diameter compared to control medium. Moreover, when combined with FSH, activin-A inhibited the growth promoted by FSH. At the end of 18 days of culture, all treatments presented antrum formation but without difference between treatments. Ultrastructural analysis confirmed the integrity of follicles cultured in FSH after 18 days. Follicles cultured in the presence of activin-A in association with FSH significantly reduced (P<0.05) levels of mRNA for ActR-IB, ActR-IIB, FSH-R and PCNA. Moreover, in follicles cultured with FSH alone, levels of mRNA for HAS 1 and HAS 2 were significantly higher (P<0.05) that in follicles cultured with activin-A in association with FSH. In addition, the level of mRNA expression for HAS-3 did not differ (P> 0.05) between treatments. In conclusion, activin-A is important for early follicular development (up to 6 days), but reduces the stimulatory effect of FSH on bovine preantral follicles after 18 days of culture in vitro. Our results also indicate that FSH is a key factor for survival and growth of bovine preantral follicles cultured in vitro for a long period (18 days). Moreover, activin-A in combination with FSH reduce the levels of mRNA for activin receptor type IB (ActR-IB), type II-B (ActR-IIB), FSH-R and PCNA after 18 days in vitro. In addition, follicles cultured in medium supplemented with FSH alone levels of mRNA for HAS-1 and HAS-2 were higher than in follicles cultured in medium supplemented by the association of activin-A and FSH.